Leveraging ddRADseq for Uncovering New Genome-Wide and Polymorphic SSR Markers in Japanese Plum (Prunus salicina Lindl.) - C. V. Acuña; N. C. Aguirre; C. V. Filippi; M. N. García; J. G. Rivas; P. V. Villalba; A. V. Gutiérrez; M. C. Martínez; T. Cerrillo; G. H. Valentini; G. Sánchez; H. E. Hopp; et al. (Plant Molecular Biology Reporter, 2025)

Concomitant medications in patients with metastatic urothelial carcinoma receiving enfortumab vedotin: real-world data from the ARON-2EV study - Ondřej Fiala; Sebastiano Buti; Kazutoshi Fujita; Alfonso Gómez de Liaño; Wataru Fukuokaya; Takahiro Kimura; Takafumi Yanagisawa; Patrizia Giannatempo; Martin Angel; Alessia Mennitto; Javier Molina-Cerrillo; Maria T. Bourlon; et al. (Clinical & Experimental Metastasis, 2025)
Patients with metastatic urothelial carcinoma (mUC) are typically elderly and often have other comorbidities that require the use of concomitant medications. In our study we evaluated the association of concomitant use of antibiotics (ATBs), proton pump inhibitors (PPIs), corticosteroids, statins, metformin and insulin with patient outcomes and we validated the prognostic role of a concomitant drug score in mUC patients treated with enfortumab vedotin (EV) monotherapy. Data from 436 patients enrolled in the ARON-2 EV retrospective study were analyzed according to the concomitant medications used at baseline. Finally, the patients were stratified into three risk groups according to the concomitant drug score based on ATBs, corticosteroids and PPIs. Statistical analysis involved Fisher exact test, Kaplan–Meier method, log-rank test, and univariate/multivariate Cox proportional hazard regression models. Inferior survival outcomes were observed in ATB users compared to non-users (OS: 7.3 months, 95%CI 5.0 − 12.3 vs 13.7 months, 95%CI 12.2 − 47.3, p = 0.001; PFS: 5.1 months 95%CI 3.3 − 17.7 vs 8.3 months, 95%CI 7.1 − 47.3, p = 0.001) and also in corticosteroid users compared to non-users (OS: 8.4 months, 95%CI 6.6 − 10.0 vs 14.2 months, 95%CI 12.7 − 47.3, p < 0.001; PFS: 6.0 months 95%CI 4.6 − 7.9 vs 8.9 months, 95%CI 7.2 − 47.3, p = 0.004). In the Cox multivariate analysis, the concomitant drug score was a significant factor predicting both OS (HR = 1.32 [95% CI 1.03 − 1.68], p = 0.026) and PFS (HR = 1.23 [95% CI 1.01 − 1.51], p = 0.044). Our findings suggest detrimental impact of concomitant use of ATBs and corticosteroids on survival outcomes and the prognostic utility of the concomitant drug score in previously treated mUC patients receiving EV.

Molecular genetic analysis of patients carrying steroid 21-hydroxylase deficiency in the Mexican population: identification of possible new mutations and high prevalence of apparent germ-line mutations - Maria Luisa Ordoñez-Sánchez; Salvador Ramírez-Jiménez; Antonio Ulises López-Gutierrez; Laura Riba; Salvador Gamboa-Cardiel; Mabel Cerrillo-Hinojosa; Nelly Altamirano-Bustamante; Raúl Calzada-León; Carlos Robles-Valdés; Fernando Mendoza-Morfin; M. T. Tusié-Luna (Human Genetics, 1998)